Barriers and perceived usefulness of an ECHO intervention for office-based buprenorphine treatment for opioid use disorder in North Carolina: A qualitative study. Issue 1 (2nd January 2021) - Shea, Christopher M.; Gertner, Alex K.; Green, Sherri L.
Abstract: Background: Medication treatment for opioid use disorder (M-OUD) is underutilized, despite research demonstrating its effectiveness in treating opioid use disorder (OUD). The UNC Extension for Community Healthcare Outcomes for Rural Primary Care Medication Assisted Treatment (UNC ECHO for MAT) project was designed to evaluate interventions for reducing barriers to delivery of M-OUD by rural primary care providers in North Carolina. A key element was tele-conferenced sessions based on the University of New Mexico Project ECHO model, comprised of case discussions and didactic presentations using a "hub and spoke" model, with expert team members at the hub site and community-based providers participating from their offices (i.e., spoke sites). Although federal funders have promoted use of the model, barriers for providers to participate in ECHO sessions are not well documented. Methods : UNC ECHO for MAT included ECHO sessions, provider-to-provider consultations, and practice coaching. We conducted 20 semi-structured interviews to assess perceived usefulness of the UNC ECHO for MAT intervention, barriers to participation in the intervention, and persistent barriers to prescribing M-OUD. Results : Participants were generally satisfied with ECHO sessions and provider-to-provider consultations; however, perceived value of practice support was less clear. Primary barriers to participating in ECHO sessions were timing and length of sessions. Participants recommended recording ECHO sessions for viewing later, and some thought incentives for either the practice or provider could facilitate participation. Providers who had participated in ECHO sessions valued the expertise on the expert team; the team's ability to develop a supportive, collegial environment; and the value of a community of providers interested in learning from each other, particularly through case discussions. Conclusions : Despite the perceived value of ECHO, barriers may prevent consistent participation. Also, barriers to M-OUD delivery remain, including some that ECHO alone cannot address, such as Medicaid and private-insurer policies and availability of psychosocial resources.